Advertisers' tactics and attitude towards advertisements: a comparison of two ethnicities - Dennis, Achil (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The paper determines to discover Iban and Chinese beliefs of the tactics that advertisers use and the overall attitude towards advertisements through a specially designed questionnaire. The study would also like to see if ethnic identification influences the ethnicsʼ beliefs and skepticism towards advertisements.